Empirical Study: Liquidity, Profitability, Company Size And Sales Growth on Capital Structure in The Indonesian Stock Exchange - Vinna Kusuma Sunnah; Nurma Gupita Dewi (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
Capital structure reflects the company’s way of determining funding sources. The purpose of the research carried out is to analyze and assess how liquidity, profitability, company size and sales growth impact the capital structure. The research population includes all food and beverage companies which have been listed on the Indonesian Stock Exchange in that time range. The sample was selected by utilizing a purposive sampling technique, while documentation method was used to obtain data. This research involved 20 companies as samples, with a total of 60 observations. To analyze the data, multiple linear regression method was used. Research findings indicate that a significant and negative influence between liquidity and profitability on capital structure, while company size shows a significant and positive influence. Meanwhile, sales growth shows a positive influence but statistically influence is not significant on capital structure.